A RIGOROUS APPROACH TO PRIORITIZING CHALLENGES OF WEB-BASED APPLICATION SYSTEMS - Qadir, Mubshra; Farid, Shahid; Bin Md Nasir, Mohd Hairul Nizam; Akbar, Atif (Malaysian Journal of Computer Science, 2021)
Web innovations are unique advancements of software engineering. They are equipped with new apparatuses, novel systems, and revolutionary plans, ready to be used by web application developers and their users. According to their importance for web application improvement, there is a need to locate a fitting approach to adapt to these challenges. Therefore, the core objective of this study is to rank the challenges that were encountered by the developers and users of web-based applications. This study contributes to knowledge by proposing a hierarchical framework for identifying and categorizing the challenges appropriately. An exhaustive list of sixty-nine challenges was formulated, based on extensive literature review. Quantitative in nature, this study uses the survey questionnaire to collect data from 87 experts in the web innovation domain. Various statistical models like the Cronbach’s Alpha, Principal Component Analysis, Stepwise, and Logistics Regression were employed to analyze the data. The stepwise regression was deployed to formulate the hierarchy of the extracted challenges. The outcome of the proposed framework would lead to a more efficient development and utilization of web applications. The limitations and future directions of this study were also discussed.